Sinergi KKN Dan Masjid: Mewujudkan Pemberdayaan Masyarakat Di Masjid Al-Muttaqin Renah Lebar - Elvira Purnamasari; Andrian Fuady; Muhammad Ali Sumantri; Anggun Dewiarti; Dian Wahyu Lia; Enjelika Marda Lensi; Meysi Dwi Saputri; Okta Riski Tata Negara; Rega Agustina; Rheinavia Putri Utami; Sintia Junita (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mosques play an important role in the life of Muslim communities, not only as places of worship but also as centers of socio-religious activities. Mosque empowerment is needed to strengthen the function of mosques in various aspects of community life. This research aims to explore and analyze community participation in empowering mosques with a narrative study regarding the implementation of mosque-based Community Service Programs (KKN) at the Al-Muttaqin Mosque, Renah Lebar. The main focus of this research is to understand how community involvement in KKN activities can influence mosque empowerment and community capacity development. The research method used is a narrative study approach which involves in-depth interviews, observation and documentation of various stakeholders, including mosque members, KKN students and the surrounding community. The research results show that community participation in mosque-based KKN programs not only improves the function and role of mosques in the community but also strengthens social ties and motivates the community to be more active in religious and social activities. This research concludes that mosque-based KKN can be an effective model for community empowerment, provided there is careful planning and good collaboration between all parties involved. It is hoped that these findings can contribute to the development of mosque-based community empowerment programs in other areas.